A study of peripheral leucocyte migration in agarose medium in inflammatory bowel disease. Issue 4 (April 1974) - Bartnik, Witold; Swarbrick, E. T.; Williams, Christopher
Abstract : The migration of peripheral leucocytes from patients with inflammatory bowel disease was investigated using an agarose plate technique and three antigenic materials: (1) the enterobacterial common antigen of Kunin; (2) extract from germ-free rat faeces; and (3) Kveim suspension from a sarcoid spleen K19. Inhibition of migration was obtained only with Kunin antigen. It was present in 11 out of 20 patients with ulcerative colitis and in four out of 20 patients with Crohn's disease but in only one out of 33 control subjects. These findings suggest the possibility that a state of cellular immunity to enterobacterial common antigen may exist in inflammatory bowel disease. Lack of cellular reactivity to extract from germ-free faeces and Kveim suspension is in contrast with the results obtained by others by means of the capillary tube method and requires further investigation.